Lithium promotes recovery after spinal cord injury - Ying-Jie Zhao (Wolters Kluwer Medknow Publications, 2022)
Lithium is associated with oxidative stress and apoptosis, but the mechanism by which lithium protects against spinal cord injury remains poorly understood. In this study, we found that intraperitoneal administration of lithium chloride (LiCl) in a rat model of spinal cord injury alleviated pathological spinal cord injury and inhibited expression of tumor necrosis factor α, interleukin-6, and interleukin 1 β. Lithium inhibited pyroptosis and reduced inflammation by inhibiting Caspase-1 expression, reducing the oxidative stress response, and inhibiting activation of the Nod-like receptor protein 3 inflammasome. We also investigated the neuroprotective effects of lithium intervention on oxygen/glucose-deprived PC12 cells. We found that lithium reduced inflammation, oxidative damage, apoptosis, and necrosis and up-regulated nuclear factor E2-related factor 2 (Nrf2) and heme oxygenase-1 in PC12 cells. All-trans retinoic acid, an Nrf2 inhibitor, reversed the effects of lithium. These results suggest that lithium exerts anti-inflammatory, anti-oxidant, and anti-pyroptotic effects through the Nrf2/heme oxygenase-1 pathway to promote recovery after spinal cord injury. This study was approved by the Animal Ethics Committee of Xi’an Jiaotong University (approval No. 2018-2053) on October 23, 2018.